Keandalan Sistem Proteksi Kebakaran pada Gedung Sentral Fakultas Pertanian Universitas Brawijaya - Paulliardi, Alethea Kalinda Xaviera; Ar. Ir. Heru Sufianto, M.Arch.St, Ph.D., IAI (Jurnal Mahasiswa Departemen Arsitektur, 2024)
Fire cases in Malang have been increasing every year. There were 66 cases of fire disaster recorded in 2021 and 77 cases recorded in 2022. In 2023, the number of cases increased by 280 percent. Brawijaya University is one of the universities in Malang. In 2020, Brawijaya University had 19 mid-rise buildings. One of Brawijaya University’s mid-rise buildings is the Central Building of the Faculty of Agriculture, which stands at six stories high. This building accommodates various activities such as administration, management, and education. There are several laboratories on the third and fourth floors, and an auditorium on the sixth floor. Fires can occur unexpectedly, even in educational facilities like Brawijaya University’s Central Building of the Faculty of Agriculture, especially considering the equipment and materials in the laboratoriums that could potentially trigger a fire. This research aims to assess the reliability of the fire protection system in Brawijaya University’s Central Building of the Faculty of Agriculture and propose strategies for improvement to prevent casualties. The methodology used in this research is descriptive and evaluative. The findings indicate that Brawijata University’s Central Building of the Faculty of Agriculture has implemented a fire protection system, but there are elements that need improvement to meet standards. Keywords: fire protection system, educational facility, mid-rise building